2015
DOI: 10.17305/bjbms.2015.409
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the presence of fungal agents in febrile neutropenic patients using different microbiological, serological, and molecular methods

Abstract: This study aimed to investigate fungal agents in febrile neutropenic patients with hematological malignancies. Direct microscopy and cultures were performed on clinical samples collected from febrile neutropenic episodes. The galactomannan (GM) antigen was tested using enzyme-linked immunosorbent assays, and Aspergillus fumigatus and Candida albicans deoxyribonucleic acid (DNA) assessed using real-time polymerase chain reaction (PCR) in consecutive serum samples. Of the 199 episodes investigated, 1.5% were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…Gram-positive cocci were isolated in 34.61% while Gram-negative bacilli were identified in 61.53% in a study by Mandal et al [51]. Fungal infections in form of aspergillosis accounted for 6% of febrile neutropenic patients in this study, similar result found in a study by Sönmez et al [52] in which aspergillosis accounted for 5.9%. Among Gram-negative bacteria, E. coli was found to be the most common culprit pathogen (46.6%) Gaytán-Martínez et al found that E. coli was the pathogen isolated mostly during episodes of primary bacteremia among patients with cancer and febrile neutropenia [53].…”
Section: Discussionsupporting
confidence: 87%
“…Gram-positive cocci were isolated in 34.61% while Gram-negative bacilli were identified in 61.53% in a study by Mandal et al [51]. Fungal infections in form of aspergillosis accounted for 6% of febrile neutropenic patients in this study, similar result found in a study by Sönmez et al [52] in which aspergillosis accounted for 5.9%. Among Gram-negative bacteria, E. coli was found to be the most common culprit pathogen (46.6%) Gaytán-Martínez et al found that E. coli was the pathogen isolated mostly during episodes of primary bacteremia among patients with cancer and febrile neutropenia [53].…”
Section: Discussionsupporting
confidence: 87%
“…18 , 19 An invasive candidosis might lead to a life threatening candidemia, especially in immune-compromised patients. 7 Here, a CAG titer of 1:8 and higher might be a valuable predictor to an increased risk for mortality in burn patients. However, an increasing CAG titer by itself has also been reported a Dumping–phenomenon in a previous study.…”
Section: Discussionmentioning
confidence: 98%
“…6 Additionally, in clinical settings, where diagnosis of candidemia leans heavily on the use of real-time PCR or PCR while these tests are not available, clinical importance of CAG titer should not be underestimated. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of invasive fungal infection is estimated to be 15-25% in high-risk patient groups, with over 90% of fungal infections attributed to Candida and Aspergillus species. Mortality rates are high, reaching 50% for Candida infections and 100% for Aspergillus infections [47]. The use of prophylactic fluconazole has led to an increase in non-albicans Candida strains.…”
Section: Discussionmentioning
confidence: 99%